Newcastle approach for the treatment of supra-intercondylar fractures in children. (February 2020) - Salvador, Jordi; Nuñez, Jorge H.; Veloso, Margarita; Castillón, Pablo; Angles, Francesc
Abstract: Purpose: The aim of this study is to evaluate the functional results of open reduction using the Newcastle approach and internal fixation for complex intra-articular distal humeral fractures in children through the report of cases. Material and methods: A retrospective case series of patients who underwent open reduction and internal fixation surgery because of a complex intra-articular distal humeral fracture using the Newcastle approach were reviewed. Minimum follow-up was 2 years. Demographic, clinical, and radiological data were analyzed. Also, Mayo Elbow Performance Score and four-point Likert scale were evaluated. Results: 2 children were included in the final analysis. In both fractures, the approach was sufficient for accurate reduction and the functional outcome on both elbows was satisfactory. The Mayo elbow score was 95 points (excellent results) and the five-point Likert scale, both patients were very satisfied with the outcomes. In the radiographic study, no necrosis or secondary deformities were observed. Conclusions: Our study provides evidence that the Newcastle approach is an alternative to perform open reduction in those children supra-intercondylar fractures that cannot be reduced using a close reduction. To our knowledge, there is not previous paper that has reported the used of this approach in the treatment in this kind of fractures.